(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Given the rapid expansion of Islamic finance on a global scale, there is significant potential for enhancing financial inclusion within Uzbekistan, a predominantly Muslim nation. While dedicated Islamic financial institutions play a vital role in this endeavor, it’s equally crucial to recognize the potential of existing traditional financial institutions to contribute by offering services consistent with Islamic finance principles. This not only improves their financial standing but also fosters inclusive growth and advances the Islamic finance landscape in Uzbekistan. The current article examines the current landscape and emerging trends in Islamic finance alongside traditional financial institutions in Uzbekistan, as well as analogous services in international contexts adhering to Islamic finance principles. Drawing from this analysis, the article presents transformative suggestions for traditional financial entities to introduce supplementary services and explore the Islamic finance market, all while maintaining their core operations intact.